Long-range ordering and local structural disordering of BiAgSe2 and BiAgSeTe thermoelectrics. Issue 42 (21st October 2021) - Huang, Weifeng; Zhu, Yingcai; Liu, Yong; Tao, Shi; Yang, Changchun; Diao, Qianshun; Hong, Zhen; Han, Haijiao; Liu, Lijuan; Xu, Wei
Abstract : Thermoelectric materials are promising for energy harvesting using waste heat. Abstract : Thermoelectric materials are promising for energy harvesting using waste heat. The thermal management of the thermoelectric materials attract scientific and technological interests. The narrow bandgap semiconductor BiAgSe2 is a good candidate for thermoelectric materials due to its ultralow thermal conductivity. The mother compound BiAgSe2 crystallizes in hexagonal symmetry at room temperature, but experiences structural transitions to cubic phase at high temperature. By contrast, the daughter compound BiAgSeTe exhibits long range ordering and crystallizes into cubic phase at room temperature. Nevertheless, the local structural disorderings due to the Bi 3+ and Ag + anti-site defects, as well as local structural distortions, are ubiquitous in both parent BiAgSe2 and BiAgSeTe. BiAgSeTe exhibits distinct transport properties owing to the disordering-induced drastic changes in the electronic band structure, as well as the scattering dictated by the point defects. It is suggested that BiAgSe2 and BiAgSeTe could be good candidates for phonon glass and crystal glass (PGEC)-type thermoelectrics.